Time and spatial aspects of movement anticipation - Borysiuk, Z.; Sadowski, J. (Biology of Sport, 2007)
Anticipation is a mental process consisting in foreseeing future events and situations based on shortening the selection stage in the information phase of sensorimotor responses. Through anticipation it is possible to program proper technical actions in a sports fight and to correct them depending on the changing conditions of a contest. Methods: 14 physically fit students took part in the experiment. The EMG measurement System was used for detection of latency time marked RT (reaction time), movement time (MT), and EMG signal value. The research aim adopted was the evaluation of the influence of advance signals on the changeability of RT, MT and EMG signal parameters in consecutive tests. Results: The results of the time anticipation test: RT - 127 ms and MT - 88 ms showed that the latent reaction time was shortened by 99 ms and the movement time by 42 ms compared to the control test. Therefore it can be stated that an earlier knowledge of the time series of signals has a greater influence on information processes than on the movement speed expressed by the MT value. Conclusion: The research work proved that the factors anticipating motor activities significantly increase their effectiveness influencing the shortening of both the reaction time and the movement itself. This phenomenon refers especially to the sensor phase, mainly to the stage of motor program selection.